Factors Associated with Nutritional Status of Pregnant Women in Cibungbulang Sub-District (International Journal of Scientific Research in Science and Technology, 2024)
Chronic energy deficiency (CED) is one of nutritional problems in pregnant women characterized by MUAC less than 23.5 cm. Based on 2018 Riskesdas, the prevalence of CED among pregnant women in Bogor Regency reached 11.22 percent. This study aimed to determine relationships between education level, employment, recovery supplementary feeding, oral and personal hygiene with nutritional status of pregnant women in Cibungbulang. This study used cross-sectional method with 195 samples selected by systematic random sampling. Almost all data, except nutritional status, were collected using interviews with questionnaires and maternal nutrition status by measuring mid-upper arm circumferences (MUAC). Most pregnant women belonged to the non-risk age (69.2%), on third trimester of pregnancy (51.8%), and had multigravida pregnancies (59.5%). Most pregnant women had completed junior high school (72.8%), did not work (88.7%), did not receive recovery supplementary feeding (85.6%), maintained oral hygiene (80%), and did not maintain personal hygiene (71.8%). A total of 15.9 percent of pregnant women had CED. There were significant relationships between recovery supplementary feeding (p=0.000) and oral (p=0.005) and personal hygiene (p=0.021) with maternal nutrition status (p<0.05). However, education level (p=0.051) and employment status (p=0.121) were not associated with maternal nutrition status (p>0.05). Recovery supplementary feeding and oral and personal hygiene were related to nutritional status of pregnant women in Cibungbulang Sub-District. The implementation and monitoring of recovery supplementary feeding should be re-invigorated.